DETERMINAN PERILAKU MEROKOK PADA REMAJA - Alamsyah, Agus; Nopianto, Nopianto (Jurnal Endurance, 2017)
Behavior smoking is behavior burn one of the products of tobacco for sucked including resulting from plants nicotina tabacum , nicotina rustica and other species or sintetisnya who its smoke ascended containing nicotine and tar. Early survey showed that 50 percent of students men in state vocational schools 5 pekanbaru consisting of the class x and xi behave smoking. Research objectives know proportion and determinan ( factors ) related to behavior smoked on male students class x and xi in state vocational schools 5 pekanbaru 2016. Research methodology quantitative analytic observational with the design cross sectional. Population were 1221 from 211 male students class x and xi.Technique the sample collection stratified random sampling by test chi square.The research results show 57,8 percent of students men class x and xi behave smoking and 42,2 % not behaving smoking. Variable are associated with behavior smoking is knowledge, attitude, extracurricular activities and cigarette advertisement. Suggested to relevant agencies to increase frequency counseling health about danger of smoking, inserting understanding danger of smoking in activities UKS and PMR and maximize media promotion health about danger of smoking. Perilaku merokok merupakan perilaku membakar salah satu produk tembakau untuk dihisap termasuk yang dihasilkan dari tanaman nicotina tabacum, nicotina rustica dan spesies lainnya atau sintetisnya yang asapnya mengandung nikotin dan tar. Survei awal menunjukan bahwa 50% siswa laki-laki di SMK Negeri 5 Pekanbaru yang terdiri dari kelas X dan XI berperilaku merokok. Tujuan penelitian mengetahui proporsi dan determinan (faktor-faktor)  yang berhubungan dengan perilaku merokok pada siswa laki-laki kelas X dan XI di SMK Negeri 5 Pekanbaru tahun 2016. Metode penelitian kuantitatif analitik observational dengan desain  cross sectional. Populasi berjumlah 1221 dengan sampel 211 siswa laki-laki kelas X dan XI. Teknik pengambilan sampel stratified random sampling dengan uji chi square. Hasil penelitian menunjukkan 57,8% siswa laki-laki kelas X dan XI berperilaku merokok dan 42,2% tidak berperilaku merokok. Variabel yang berhubungan dengan perilaku merokok adalah pengetahuan, sikap, kegiatan ekstrakurikuler dan iklan rokok. Disarankan ke instansi terkait untuk meningkatkan frekuensi penyuluhan kesehatan tentang bahaya rokok, memasukan pemahaman bahaya rokok ke dalam kegiatan UKS dan PMR serta memaksimalkan media promosi kesehatan tentang bahaya rokok.